Concurrent Training and Detraining: The Influence of Different Aerobic Intensities - Sousa, António C. (2020)
Sousa, AC, Neiva, HP, Gil, MH, Izquierdo, M, Rodríguez-Rosell, D, Marques, MC, and Marinho, DA. Concurrent training and detraining: the influence of different aerobic intensities. J Strength Cond Res XX(X): 000-000, 2018-The aim of this study was to verify the effects of different aerobic intensities combined with the same resistance training on strength and aerobic performances. Thirty-nine men were randomly assigned to a low-intensity group (LIG), moderate-intensity group (MIG), high-intensity group (HIG), and a control group. The training program consisted of full squat, jumps, sprints, and running at 80% (LIG), 90% (MIG), or 100% (HIG) of the maximal aerobic speed for 16-20 minutes. The training period lasted for 8 weeks, followed by 4 weeks of detraining. Evaluations included 20-m sprints (0-10 m: T10; 0-20 m: T20), shuttle run, countermovement jump (CMJ), and strength (1RMest) in full squat. There were significant improvements from pre-training to post-training in T10 (LIG: 4%; MIG: 5%; HIG: 2%), T20 (3%; 4%; 2%), CMJ (9%; 10%; 7%), 1RMest (13%; 7%; 8%), and oxygen uptake (V[Combining Dot Above]O2max; 10%; 11%; 10%). Comparing the changes between the experimental groups, 1RMest gains were significantly higher in the LIG than HIG (5%) or MIG (6%). Furthermore, there was a tendency for higher gains in LIG and MIG compared with HIG, with "possibly" or "likely" positive effects in T10, T20, and CMJ. Detraining resulted in performance decrements, but minimal losses were found for V[Combining Dot Above]O2max in LIG (-1%). Concurrent training seems to be beneficial for strength and aerobic development regardless of the aerobic training intensity. However, choosing lower intensities can lead to increased strength and is recommended when the cardiorespiratory gains should be maintained for longer.